Neonatal Risk Factors for ASD and ADHD and Therapeutic Regimens for their Management in Children and Adolescent - R. Mohammad, Shumoos; M. Anwer, Zinah; A. Saleem, Zainab (Journal of the Faculty of Medicine Baghdad, 2024)
Background:  Attention deficit hyperactivity disorder (ADHD) and autism spectrum disorder (ASD) are both neurodevelopmental disorders that affect children early in life. Both conditions have a complicated origin.Objectives: This study aims to evaluate the neonatal complications linked with ASD and ADHD and to outline the utilization of psychotropic medications in the management of children and adolescents with ASD.Methods: This study was conducted from January to April 2022 at the National Center for Autism/Medical City Complex in Baghdad. It involved 120 children with neurodevelopmental disorders and 120 control participants. A questionnaire was used to collect the data, which was then analyzed using SPSS 25.Results: Five perinatal factors have significant associations with child behavioral disorders, as indicated by a P-value of less than 0.05. These factors are Low birth weight (LBW), newborn complications, preterm birth, being the last child, and children delivered via a cesarean section. Additionally, the types of behavioral disorders have significant associations with the use of psychotropic medications. Around 50% of children with both ASD and ADHD, as well as children with ADHD alone, have used psychotropic medications. By comparison, only about 27% of children with ASD have used these medications.Conclusions: Neonatal risk factors may be linked to neurodevelopmental disorders. Medications are used to manage ASD and ADHD in children and youth.